The taxation of the "sharing economy" in South Africa - Gumbo, Wadzanai Charisma (Rhodes University, Faculty of Commerce, Department of Accounting, 2019)
The research examined whether the services provided by the "sharing economy" platforms are adequately dealt with by the current South African tax systems. In addressing this main goal, the research analysed how the South African tax systems deal with the income and expenses of Uber, Airbnb and their respective service providers. The research also investigated how South Africa could classify "sharing economy" workers and how this would affect the deductibility of the worker's expenses. A brief analysis was made of the taxation of the "sharing economy" businesses in Australia and the United States of America. These countries have implemented measures to effectively deal with regulating the "sharing economy" businesses. An interpretative research approach was used to provide clarity on the matter. Documentary data used for the research consists of tax legislation, case law, textbooks, commentaries, journal articles and theses. The research concluded that the current taxation systems have loopholes that are allowing participants in the "sharing economy" to avoid paying tax in South Africa. The thesis recommends that the legislature could adopt certain measures applied in Australia and the United States of America to more effectively regulate "sharing economy" in South African and remedy the leakages the current tax systems suffer, causing SARS to lose potential revenue.
Keywords: Corporations -- Taxation; Taxation -- South Africa; Value-added tax -- Law and legislation -- South Africa; Double taxation -- South Africa; Tax evasion -- South Africa; Income tax -- Law and legislation -- South Africa; Tax administration and procedure -- South Africa